GIS and multi-criteria decision analysis in resource assessment and site selection of mini-hydropower the case of Palawan - Seranilla, Justin Jesse L.
Electricity in the province of Palawan, Philippines is currently sourced almost exclusively from diesel and bunker fuel oil and only about 50% of households are connected to the provincial electricity grid, about 13% of which experience less than 24 hours of service per day. The development of mini-hydropower facilities, with lower CO2 emissions and competitive cost, is one of the potential solutions sought by the local government in meeting the province's energy needs, considering it as a potential baseload in the Palawan Island Power Development Plan. This study determines the potential of mini-hydropower in mitigating the energy problem in Palawan by identifying suitable mini-hydropower sites across the province. To screen locations with sufficient flow and gradient for mini-hydropower operation, a hydrologic model covering Palawan was developed using Hydropower Potential Assessment Tool (HPAT), a MATLAB-based program which uses publicly available data and local streamflow conditions as inputs. The output of the program was used to developed a power potential map that locates suitable sites for mini-hydropower development. The results showed that the total mini-hydropower potential for the whole province is 47.449 MW. Overall, there are 299 potential sites as determined by the program, and the top three sites have capacities of 1,540 kW, 830 kW, and 798 kW, located at Brgy. Taritien in Narra, Brgy. San Isidro in Narra, and Brgy. Yolo King Ranch in Coron, respectively. Multi-Criteria Decision Analysis (MCDA) was later employed to evaluate the suitability of mini-hydropower for selected locations and determine mini hydropower technology's comparative acceptability over other energy.